Estimation of flow rate calculation errors on the example of five rapid response catchments in the Mecsek Hills - Hegedűs, Péter; Czigány, Szabolcs; Pirkhoffer, Ervin; Balatonyi, László; Ronczyk, Levente (Hungarian Geographical Bulletin, 2013)
Today flash floods are one of the most significant extreme weather-related natural hazards. Due to the global climate change and altered land use, intense runoff and flash floods may exert catastrophic hydrologic impacts on developed areas. To measure and observe runoff - affecting environmental factors we have calculated characteristic flow values (CFV) with five empirical equations for five selected watersheds in the Mecsek Hills, SW Hungary. CFV’s were then compared with measured characteristic Qmax values of 5, 10, 20, 33 and 100-year return period. From the empirical equations the Rational method was the most accurate while the largest differences between the calculated and measured values was observed for the Csermák-method. Nonetheless, determination of the input parameters for the Rational and Virág methods is rather challenging, thus, for practical applications, the Korismethod was found to be the most applicable equation to determine CFVs. Additionally, the median Koris errors showed a strong exponential correlation with the 5% specific runoff . If specific runoff could be estimated for any given outflow point, then error-specific runoff functions could be used to increase the accuracy of the Koris calculation method. To further increase the accuracy of CFVs for selected outflow points and cross sections, area and watershed-specific variables need to be included in the equation to account for topography, land use and soil properties.